Association of Immunoglobulin G3 Hinge Region Length Polymorphism With Cerebral Malaria in Ghanaian Children. (28th October 2021) - Kyei-Baafour, Eric; Kusi, Kwadwo A; Arthur, Fareed K N; Sarkodie-Addo, Tracy; Theisen, Michael; Dodoo, Daniel; Adu, Bright
Abstract: Cerebral malaria (CM) may cause death or long-term neurological damage in children, and several host genetic risk factors have been reported. Malaria-specific immunoglobulin (Ig) G3 antibodies are crucial to human immune response against malaria. The hinge region of IgG3 exhibits length polymorphism (with long [L], medium [M], and short [S] alleles), which may influence its functionality. We studied IgG3 hinge region length polymorphisms in 136 Ghanaian children with malaria. Using logistic regression models, we found that children with the recessive MM allotype encoding medium IgG3 hinge region length had an increased risk of CM (adjusted odds ratio, 6.67 [95% confidence interval, 1.30–34.32]; P =.004) . This has implications for future epidemiological studies on CM. Abstract : The hinge region of immunoglobulin (Ig) G3 exhibits length polymorphism (long, medium, and short alleles), which may influence its functionality. We found an increased risk of cerebral malaria in Plasmodium falciparum –infected Ghanaian children with medium IgG3 hinge region length.